Alternative energy in Ukraine. System dynamics methodology in RES research - Bitkova, T.; Manakhov, K. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2024)
The growing demand for electricity, which is expected to double by 2030 and quadruple by 2050 compared to 2000, underlines the urgent need for widespread deployment of renewable energy sources (RES) such as wind, solar, bioenergy, hydro and geothermal ones. Initiatives of many countries reflect the growing recognition of the need of transition to sustainable energy systems. According to the UN, Sustainable Development Goal 7 is "to ensure access to affordable, reliable, sustainable and modern energy for all". The paper examines the foreign experience of mixed energy development strategies and discusses the hypotheses of RES impact on key processes taking place in various spheres of life. In Ukraine, the transition to renewable energy is vital due to not only ecological or economic necessity, but also to a strategic one. According to the updated energy strategy of Ukraine until 2030, alternative energy should make up 25% of the total energy production, which corresponds to the country’s obligations to the European Energy Community. But Ukraine faces a number of economic barriers that prevent deployment of renewable energy sources. These include high initial investment costs, unstable public policy frameworks and limited access to necessary financing, which together create a difficult investment climate that discourages domestic and foreign investors. By the start of the war in 2022, renewable energy sources accounted for about 13.4% of total energy production in Ukraine. However, the destruction of energy infrastructure throughout the country, including that of the renewable energy sector, led to a sharp decrease in this indicator up to 5-6%. A special attention in this study is paid to the use of the System Dynamis (SD) concept of simulation in RES research. Analysis of the latest publications and reference models testify to the effectiveness of the SD methodology and allowed to form the base model assumptions. Paper presents a structural SD model for the analysis of the implementation of renewable energy in Ukraine, taking into account the complex interaction of economic, social and environmental challenges to assess the long-term potential consequences of the transition to RES.